N-Acetylcysteine Prevents Hypertension via Regulation of the ADMA-DDAH Pathway in Young Spontaneously Hypertensive Rats. (17th December 2013) - Fan, Nai-Chia; Tsai, Chih-Min; Hsu, Chien-Ning; Huang, Li-Tung; Tain, You-Lin
Abstract : Asymmetric dimethylarginine (ADMA) reduces nitric oxide (NO), thus causing hypertension. ADMA is metabolized by dimethylarginine dimethylaminohydrolase (DDAH), which can be inhibited by oxidative stress. N-Acetylcysteine (NAC), an antioxidant, can facilitate glutathione (GSH) synthesis. We aimed to determine whether NAC can prevent hypertension by regulating the ADMA-DDAH pathway in spontaneously hypertensive rats (SHR). Rats aged 4 weeks were assigned into 3 groups (n = 8 /group): control Wistar Kyoto rats (WKY), SHR, and SHR receiving 2% NAC in drinking water. All rats were sacrificed at 12 weeks of age. SHR had higher blood pressure than WKY, whereas NAC-treated animals did not. SHR had elevated plasma ADMA levels, which was prevented by NAC therapy. SHR had lower renal DDAH activity than WKY, whereas NAC-treated animals did not. Renal superoxide production was higher in SHR than in WKY, whereas NAC therapy prevented it. NAC therapy was also associated with higher GSH-to-oxidized GSH ratio in SHR kidneys. Moreover, NAC reduced oxidative stress damage in SHR. The observed antihypertensive effects of NAC in young SHR might be due to restoration of DDAH activity to reduce ADMA, leading to attenuation of oxidative stress. Our findings highlight the impact of NAC on the development of hypertension by regulating ADMA-DDAH pathway.